Analyses of technological and biochemical parameters related to the HTC phenomenon in carioca bean genotypes by the use of PCA. (January 2016) - Siqueira, Beatriz S.; Bassinello, Priscila Z.; Malgaresi, Gabriel; Pereira, Wendell J.; Fernandes, Kátia F.
Abstract: Carioca beans are subjected to the hard-to-cook phenomena (HTC), which results in loss of technological and sensorial qualities. To better elucidate this postharvest hardening process, changes in technological and biochemical properties of grains during storage at 40 °C and 75% relative humidity were investigated, and the results were analyzed using Principal Component Analysis (PCA). Results showed that the hardening process occurs at different intensity for each genotype, and those more susceptible to HTC presented higher water absorption index (WAI) and peroxidase activity. During the storage period, oxidoreductases remained active and total phenol content increased for all genotypes. PCA explained 92.2% of total variance and grouped hardness, cooking time and WAI on PC1 (67.8%) and peroxidase activity and total phenol content on PC2 (24.4%). PCA showed that the technological parameter more related to the HTC is WAI and that hardness observed in genotypes during storage cannot be attributed to changes in the total phenol content nor to oxidorreductase activities. Highlights: Bean genotypes present different susceptibilities to the HTC phenomenon. Genotypes susceptible to HTC presented higher water absorption index. Peroxidase and polyphenolxidase remained active along the storage. Genetic variability should be considered during studies of aging process. Peroxidase and total phenol content are not directly related to HTC.